BUSINESS STRATEGY TO INCREASE MARKET SHARE OF BOTTLED DRINKING WATER BRAND AQUA IN MODERN TRADE CHANNEL - Diajeng Diska Ayudia Azani; Wulan Asti Rahayu (Universitas Trunojoyo Madura, 2023)
Bottled drinking water is one of the markets that continues to grow in Indonesia. The development of this industry is in line with the increase in population. Every resident needs drinking water as a basic need, coupled with the absence of a tap water source that is consumable. As one of bottled drinking water brand, AQUA is the market leader with a combined share of modern and traditional trade channels of 50.6% in December 2022. Along with high market demand, other brands are also participating in tough competition in this industry, both local, national, and international players such as LeMinerale, Nestle Pure Life, Crystalline, and others. Despite being the pioneer and market leader, AQUA's share slowly declines periodically from year to year. This study uses internal and external data analysis to formulate AQUA's business strategy in order to maintain and increase market share. The results of AQUA's internal and external situations are then summarized through the SWOT matrix, which is then re-analyzed and formulated into the TOWS matrix, then connected with the results of the VRIO analysis, Five Forces Analysis, Competitors Analysis and 7Ps's Marketing Mix. The research analysis data involves a survey to 418 respondents who actively decide and purchase bottled drinking water in minimarket or supermarkets in the past one month and an in-depth interview. The hypothesis result of the research which was obtained using SPSS is that significant predictor variables which are quality, price, packaging design, and findability, are able to explain the response variable, namely the AQUA purchase decision of 30.2%. Meanwhile, the remaining 69.8% is explained by other variables such as brand image, mineral and nutrient content, health, and other factors that can influence AQUA purchasing decision variables. Based on the internal and external analysis result, several strategies are proposed using the marketing mix approach to increase the market share of AQUA.